2009
DOI: 10.1159/000257515
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrophosphate Transporter ANKH is Expressed in Kidney and Bone Cells and Colocalises to the Primary Cilium/Basal Body Complex

Abstract: Background/Aims: ANKH encodes a putative pyrophosphate transporter named ANKH, which regulates tissue calcification. ANKH is a transmembrane protein with at least 8 predicted transmembrane domains. Sequence analysis reveals a possible cilial localisation motif immediately after the last transmembrane segment. Here we aim to determine the subcellular localisation of ANKH in ciliated epithelial cells and murine tissue and identify colocalisation using ciliary/basal body markers. Methods: Using murine kidney, ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Kwon et al found that primary cilia mediate the osteogenic and anti-resorptive responses of dynamic fluid flow depending on the decreases of intracellular cAMP levels and adenylyl cyclase 6 located at primary cilium [48]. Carr et al reported the human homolog of the mutated gene in the ank/ank mouse (ANKH), a widely expressed protein limiting and regulating calcification within bones, is expressed in basal body of primary cilium in the osteoblast cell line MC3T3-E1 [49]. Xiao et al shown that polycystin-1 (PC1) plays an important role in skeletogenesis through regulation of the bone-specific transcription factor Runx2-II, which co-localizes with the calcium channel polycystin-2 (PC2) in primary cilia of MC3T3-E1 osteoblasts [50].…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al found that primary cilia mediate the osteogenic and anti-resorptive responses of dynamic fluid flow depending on the decreases of intracellular cAMP levels and adenylyl cyclase 6 located at primary cilium [48]. Carr et al reported the human homolog of the mutated gene in the ank/ank mouse (ANKH), a widely expressed protein limiting and regulating calcification within bones, is expressed in basal body of primary cilium in the osteoblast cell line MC3T3-E1 [49]. Xiao et al shown that polycystin-1 (PC1) plays an important role in skeletogenesis through regulation of the bone-specific transcription factor Runx2-II, which co-localizes with the calcium channel polycystin-2 (PC2) in primary cilia of MC3T3-E1 osteoblasts [50].…”
Section: Discussionmentioning
confidence: 99%
“…Localisation studies may suggest new ways in which to investigate the functions of ANKH. We have shown that ANKH localises to the primary cilium and basal body, as well as the apical membrane, of renal epithelial cell lines and murine renal tissue [14]. This places ANKH in a very suitable position from which to sense luminal PPi in the urine (fig.…”
Section: Generation Of Luminal Ppi In the Kidneymentioning
confidence: 99%
“…Experimental models also provided data supporting a link between adverse intrauterine environment and adult disease. Both uteroplacental insufficiency and calorie restriction in pregnant rats led to high blood pressure in their adult offspring [33]. We have previously shown that a low maternal protein diet during pregnancy results in lower kidney index, glomeruli number and decreased glomerular filtration rate in IUGR offspring, with an increased incidence of hypertension [8].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins, including IFT80, IFT88and IFT144, belong to the primary cilium complex A (144) and B(80,88) module [34]. The primary cilium, a slim microtubule-based organelle that projects from the surface of vertebrate cells, has been located on almost every mammalian cell type [33]. Cilia are essential for certain developmental signaling pathways and mechanosensory functions, like detecting flow or mechanical movement and inducing an influx of Ca 2+ [24].…”
Section: Discussionmentioning
confidence: 99%